1999
DOI: 10.1101/lm.6.6.572
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between the Effects of Damage to Perirhinal Cortex and Area TE

Abstract: Perirhinal cortex and area TE are immediately adjacent to each other in the temporal lobe and reciprocally interconnected. These areas are thought to lie at the interface between visual perception and visual memory, but it has been unclear what their separate contributions might be. In three experiments, monkeys with bilateral lesions of the perirhinal cortex exhibited a different pattern of impairment than monkeys with bilateral lesions of area TE. In experiment 1, lesions of the perirhinal cortex produced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
234
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(256 citation statements)
references
References 50 publications
17
234
5
Order By: Relevance
“…Recently, Pascalis and Bachevalier (1999) showed that adult monkeys with neonatal hippocampal lesions showed preference for novelty at short delays of 10 s, but not at longer delays of 30 s to 24 h, whereas normal monkeys showed novelty preference at all delays. Consistent with this study, other studies of monkeys with selective lesions within the medial temporal lobe, have shown that novelty preference depends on the integrity of the hippocampal formation (Zola et al, 2000) as well as the perirhinal cortex (Buffalo et al, 1999). In humans, McKee and Squire (1993), using the VPC task, have shown that amnesic patients with relatively selective hippocampal damage also show abnormal novelty preference.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, Pascalis and Bachevalier (1999) showed that adult monkeys with neonatal hippocampal lesions showed preference for novelty at short delays of 10 s, but not at longer delays of 30 s to 24 h, whereas normal monkeys showed novelty preference at all delays. Consistent with this study, other studies of monkeys with selective lesions within the medial temporal lobe, have shown that novelty preference depends on the integrity of the hippocampal formation (Zola et al, 2000) as well as the perirhinal cortex (Buffalo et al, 1999). In humans, McKee and Squire (1993), using the VPC task, have shown that amnesic patients with relatively selective hippocampal damage also show abnormal novelty preference.…”
Section: Introductionsupporting
confidence: 89%
“…In monkeys, a deficit has been observed after a 10 s delay following a specific lesion of the hippocampus (Zola et al, 2000), or after a lesion of the perirhinal cortex (Buffalo et al, 1999), or after a lesion of the hippocampal formation (Pascalis & Bachevalier, 1999). A lesion of the area TE led to a deficit without delay (Buffalo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This is because these cortices would not be available to support a context representation and the hippocampal formation would be deprived of the information it needs to make its contribution to contextual fear. The literature supports this analysis (Corodimas and LeDoux 1995;Buffalo et al 1999;Bucci et al 2000Bucci et al , 2002. Note this pattern of results, damage to these regions both before and after training impairs contextual fear conditioning differs from that associated with damage to the hippocampal formation because contextual fear conditioning is spared if the hippocampal formation is damaged before conditioning.…”
Section: Defining the Neocortical Systemsupporting
confidence: 57%
“…In rats there is a deficit in processing positive priming for features of visual objects (a component of perceptual memory system), but the rats performed well in positive priming for spatial location (Kesner, unpublished observations). In monkeys deficits for visual objects and in a working memory task and visual paired comparison task were observed following TE2 deficits suggesting that TE2 cortex may play an important role in visual perceptual processing (Buffalo et al, 1999). It can also be shown that lesions of the inferotemporal cortex in monkeys and humans and temporal cortex (TE2) in rats result in visual object discrimination problems (Dean, 1990;Fuster,1995;Gross, 1973;McCarthy & Warrington, 1990;Weiskrantz & Saunders, 1984), suggesting that the inferotemporal or TE2 may play an important role in mediating long-term representations of visual object information.…”
Section: Sensory-perceptual Attributementioning
confidence: 99%